Att leva och sälja sin dröm: Livsstilsföretagaren mellan familjeliv, marknadoch politisk retorik (Sociologisk Forskning, 2014)
Living and selling a dream: Lifestyle entrepreneurship in the intersection between family, market and political rhetoricThe article focuses on lifestyle entrepreneurship, characterised by a balancing work between personal lifestyle motives and economic motives. It builds on a qualitative study of business owners who have realized a life dream of starting a countryside business in the tourism and hospitality industry in Sweden. Through the notion of ”balancing work”, the analysis focuses on the tension between a personal life sphere and a market. In particular, the analysis highlights how the notion of ”the life dream” emerges as a narrative practice of self-realization, simultaneously as it is offered as an experience product. The analysis demonstrates how the entrepreneurs balance between personal stories of togetherness and marketing practices, between images of right and wrong commodification, and between constraining working conditions and a popular image of the successful entrepreneur, reinforced by a political discourse on rural entrepreneurship. It is concluded that balancing work between personal identities and economic practices is a practice of valuation, offering new insights into working conditions and markets situated in the intersection between markets and personal life spheres.
Keywords: Lifestyle entrepreneur; rural tourism; valuation; self-realization; life dream